Cytotaxonomic investigations on some Lathyrus L. species growing in eastern Mediterranean and southern Aegean regions - II - Sahin, A; Genç, H; Bagci, E (Soc Botanique France, 2000)
In this study, some natural Lathyrus L. species growing in eastern Mediterranean and south Aegean regions have been investigated cytotaxonomically. Morphology and chromosome number and morphometries of the 8 taxa belonging to the Lathyrus genus, including Lathyrus sativus, L. stenopyhllus, L. nissolia, L. hirsutus, L. chloranthus, L. aphaca var. affinis, L. aphaca var, modestus and L. aphaca var. pseudoaphaca, have been studied by using karyological and numeric taxonomical techniques. Data obtained chromosome measurements were analysed by using cluster analysis. The chromosome number of these species have been found as 2n = 14. The results were considered in conjunction with the literature and karyological analysis results.
Keywords: Lathyrus; cytotaxonomy; chromosome; karyotype; cluster analysis